IMOM ISMOIL AL-BUXORIYNING “AL ADAB AL MUFRAD” ASARIDA MA‟NAVIY-AXLOQIY FIKRLARNI O„RGANISH MAZMUNI - Saidnazarova Gulshan Bolta qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article provides a brief review of Imam Ismail al-Bukhari's life, scientific activities, and works, as well as the study of Imam Ismail al-Bukhari's activities, including the essence of the reforms implemented by our country's president.